2009
DOI: 10.1021/nn900574r
|View full text |Cite
|
Sign up to set email alerts
|

Control of Phase in Phosphide Nanoparticles Produced by Metal Nanoparticle Transformation: Fe2P and FeP

Abstract: The transformation of Fe nanoparticles by trioctylphosphine (TOP) to phase-pure samples of either Fe(2)P or FeP is reported. Fe nanoparticles were synthesized by the decomposition of Fe(CO)(5) in a mixture of octadecene and oleylamine at 200 degrees C and were subsequently reacted with TOP at temperatures in the region of 350-385 degrees C to yield iron phosphide nanoparticles. Shorter reaction times favored an iron-rich product (Fe(2)P), and longer reaction times favored a phosphorus-rich product (FeP). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 28 publications
(77 reference statements)
9
105
0
Order By: Relevance
“…24 Transmission electron microscopy (TEM) images ( Figure 1) indicated the formation of spherical, hollow particles with an average diameter of 13 ( 2 nm. The corresponding high-resolution TEM (HRTEM) image ( Figure 1b) revealed that the hollow particles were single crystalline and faceted and are therefore morphologically similar to other transitionmetal phosphide nanoparticles formed by chemically transforming metal seed particles into phosphides using TOP.…”
Section: Resultsmentioning
confidence: 99%
“…24 Transmission electron microscopy (TEM) images ( Figure 1) indicated the formation of spherical, hollow particles with an average diameter of 13 ( 2 nm. The corresponding high-resolution TEM (HRTEM) image ( Figure 1b) revealed that the hollow particles were single crystalline and faceted and are therefore morphologically similar to other transitionmetal phosphide nanoparticles formed by chemically transforming metal seed particles into phosphides using TOP.…”
Section: Resultsmentioning
confidence: 99%
“…Li is likely either intercalated into the Zn seeds or amorphous Sb. Powder XRD data of a '0 min' sample (removed and isolated immediately upon injection) does 55,[57][58][59][60][61][62][63] Scheme 2. Mechanism of formation h*-LiZnSb.…”
Section: Resultsmentioning
confidence: 99%
“…Controlled compositions, i.e., metal-rich or phosphorus-rich, are achievable by varying the reaction time/ temperature or using inverse cannulation of metal-nanoparticle/hot TOP. [ 24 ] This was developed as a general approach for the synthesis of phosphides and is applicable to a wide range of transition metals, i.e., those with 3d, 4d, 5d structures including Ni 2 P, FeP, palladium phosphide, and platinum phosphide. The resultant nanoparticles/nanorods with a particle size ranging from several nm to ≈20 nm have attractive attributes of good uniformity and crystallinity, and the well-defi ned nanostructures are potentially ideal for electrocatalysis.…”
Section: Organic Phosphinementioning
confidence: 99%